2009
DOI: 10.1080/87565640903265137
|View full text |Cite
|
Sign up to set email alerts
|

Thalamo-Striatal T2-Weighted Hyperintensities (Unidentified Bright Objects) Correlate With Cognitive Impairments in Neurofibromatosis Type 1 During Childhood

Abstract: Learning disabilities represent the main childhood complication in neurofibromatosis type 1 (NF1). Patients frequently exhibit T2-weighted hyperintensities called unidentified bright objects (UBOs) on brain magnetic resonance imaging (MRI), with unclear relationship to such cognitive disabilities. This study aimed to determine whether thalamo-striatal UBOs correlate with cognitive disturbances. Thirty-seven NF1 children were studied: 24 with UBOs (18 of which were thalamo-striatal UBOs), and 13 without UBOs. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 35 publications
4
33
1
1
Order By: Relevance
“…We recommend the evaluation by brain MRI in children with NF1 during early childhood, after the second year, before the eighth year, or at the time of establishing the definitive clinical diagnosis if it is established after the previously mentioned age. Brain MRI can confirm the presence of T2-hyperintensities that, apart from their diagnostic value, can contribute to NF1 cognitive impairments through thalamo-cortical dysfunction (18). The recent studies have suggested that T2-hyperintesities may represent pathological foci of hyperplastic or dysplastic glial proliferation with vacuolar or spongiotic changes, with fluid-filled, coalescted, or conflated vacuoles (19).…”
Section: Discussionmentioning
confidence: 99%
“…We recommend the evaluation by brain MRI in children with NF1 during early childhood, after the second year, before the eighth year, or at the time of establishing the definitive clinical diagnosis if it is established after the previously mentioned age. Brain MRI can confirm the presence of T2-hyperintensities that, apart from their diagnostic value, can contribute to NF1 cognitive impairments through thalamo-cortical dysfunction (18). The recent studies have suggested that T2-hyperintesities may represent pathological foci of hyperplastic or dysplastic glial proliferation with vacuolar or spongiotic changes, with fluid-filled, coalescted, or conflated vacuoles (19).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have attempted to examine the relationship between the presence of T2-hyperintensities (T2Hs), a common neuroimaging finding in NF1, and neurocognitive deficits in children with NF1. While the presence and total number of T2Hs has been inconsistently associated with reductions in cognitive functioning in NF1 study populations, [13][14][15][16] several studies have demonstrated a strong relationship between the presence of discrete thalamic T2Hs and reduced cognition. [15][16][17] Other reported deficits associated with T2Hs, specifically in the cerebellum and globus pallidus, have not been reliably replicated.…”
mentioning
confidence: 99%
“…Entretanto, alguns estudos mostram uma possível associação entre a presença dos UBOs e a disfunção cognitiva (2)(3)(4)6,(11)(12)(13) . Isso poderia acontecer especialmente na presença de envolvimento do tálamo (14)(15)(16) e, talvez, se constituísse em um bom preditor de disfunção cognitiva na idade adulta (5,17) . Outros trabalhos têm também associado os UBOs a alterações no desempenho da motricidade fina (12) .…”
Section: Discussionunclassified